Valley of decisions : biography and essays in honour of Hon. Justice Iorhemen Hwande, OFR, Chief Judge, Benue State. - Hwande, Iorhemen (Safari Books Ltd, 2012)
In a tribute to Hon. Justice Iorhemen Hwande CFR, Chief Judge of Benue State, this book includes contributions from a variety of scholars from Nigeria.